No impact of performance-based financing on the availability of essential medicines in Burkina Faso: a mixed-methods study - Lohmann, Julia; Brenner, Stephan; Koulidiati, Jean-Louis; Somda, Serge M. A.; Robyn, Paul Jacob; De Allegri, Manuela (PLoS global public health, 2022)
Access to safe, effective, and affordable essential medicines (EM) is critical to quality health services and as such has played a key role in innovative health system strengthening approaches such as Performance-based Financing (PBF). Available literature indicates that PBF can improve EM availability, but has not done so consistently in the past. Qualitative explorations of the reasons are yet scarce. We contribute to expanding the literature by estimating the impact of PBF on EM availability and stockout in Burkina Faso and investigating mechanisms of and barriers to change. The study used an explanatory mixed methods design. The quantitative study component followed a quasi-experimental design (difference-in-differences), comparing how EM availability and stockout had changed three years after implementation in 12 PBF and in 12 control districts. Qualitative data was collected from purposely selected policy and implementation stakeholders at all levels of the health system and community, using in-depth interviews and focus group discussions, and explored using deductive coding and thematic analysis. We found no impact of PBF on EM availability and stockouts in the quantitative data. Qualitative narratives converge in that EM supply had increased as a result of PBF, albeit not fully satisfactorily and sustainably so. Reasons include persisting contextual challenges, most importantly a public medicine procurement monopoly; design challenges, specifically a disconnect and disbalance in incentive levels between service provision and service quality indicators; implementation challenges including payment delays, issues around performance verification, and insufficient implementation of activities to strengthen stock management skills; and concurrently implemented policies, most importantly a national user fee exemption for children and pregnant women half way through the impact evaluation period. The case of PBF and EM availability in Burkina Faso illustrates the difficulty of incentivizing and effecting holistic change in EM availability in the presence of strong contextual constraints and powerful concurrent policies.